Efficacy of Oral Itraconazole in the Treatment of Seborrheic Dermatitis - Khondker, L; Choudhury, AM; Wahab, MA; Khan, MSI (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Background: Seborrheic dermatitis is a common papulosquamous dermatosis and occurring in 2% to 5% of the population. The prevalence of seborrheic dermatitis among HIV-positive and AIDS patients between 34% and 83%. The anti-inflammatory activity of oral itraconazole and efficacy on Malessezia suggests that itraconazole capsule will be the first oral treatment option in future in seborrheic dermatitis. Unfortunately there is no data base study with the efficacy of oral itraconazole for the treatment of seborrheic dermatitis over Bangladeshi people. Objectives: To evaluate the efficacy of itraconazole in the treatment of Seborrheic dermatitis. Methods: This was an interventional type of study and total thirty seven patients of seborrheic dermatitis from department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU) was enrolled. The study was carried out for a period of two years from January 2008 to December 2009 and purposive type non-probability sampling technique was followed in this study. Results: The scoring of seborrhea was 6.33±1.15 before treatment and 4.33 ±3.21 after treatment, scoring of itching was 6.66 ±1.49 before treatment and 3.61 ±2.70 after treatment and scoring of greasy crust was 7.12 ±2.70 before treatment and 4.00 ±3.16 after treatment. It was observed that before treatment, erythema was severe in 43.2% cases, moderate in 51.4% cases and mild type erythema was present in 5.4% cases. And after treatment, 29.7% had severe type erythema, no patient had moderate type erythema, only 43.2% had mild type and 27% cases had no erythema at all. Before treatment, papular eruption was severe in 27% cases, moderate in 54.1% cases and only 18.9% had mild type papular eruption. But after treatment, 10.8% had severe type, 18.9% had moderate, 51.4% had mild and 18.9% had no papular eruption at all. It was observed that before treatment, squamation was severe in 37.8% cases and moderate in 62.2% cases. But after treatment, 18.9% had severe type squamation, 10.8% had moderate, 45.9% had mild and 24.3% had no squamation. Improvement was shown in 26(70.27%) cases and 11(29.73%) cases shown no improvement at all. Conclusion: The study suggests that oral itraconazole has significant efficacy profile for treatment option of seborrheic dermatitis. DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11326 J Bangladesh Coll Phys Surg 2011; 29: 201-206